Looking for a job: is there any homogeneity among those not seeking work? - Elisabetta Marzano (University of Essex, Institute for Social and Economic Research (ISER), 2003)
In this work we focus on the British labour force, using data from the BHPS (British Household Panel Survey). The goal is to examine whether there are statistically significant differences between the unemployed and those out of the labour force in the transition rate into employment. Using logistic regression for a pooled cross section time series sample we are able to define 4 different groups: Seeking Out of Work, Attached Out of Work, Unemployed Not Seeking, and Voluntary Out of Work. We find that these groups are characterised by very different transition rates into employment, which cannot be explained simply by the active search for a job.
Keywords: 330